2002
DOI: 10.1109/tcapt.2002.808011
|View full text |Cite
|
Sign up to set email alerts
|

Dynamically inserting, operating, and eliminating thermal sensors of FPGA-based systems

Abstract: In this paper, a new thermal monitoring strategy suitable for field programmable logic array (FPGA)-based systems is developed. The main idea is that a fully digital temperature transducer can be dynamically inserted, operated, and eliminated from the circuit under test using run-time reconfiguration. A ring-oscillator together with its auxiliary blocks (basically counting and control stages) is first placed in the design. After the actual temperature of the die is captured, the value is read back via the FPGA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
52
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 96 publications
(52 citation statements)
references
References 7 publications
0
52
0
Order By: Relevance
“…8 is used, this study is found in [12] for T=25 °C, f=1 MHz. As an example it can be assumed that fa 1 = fc 1 = 1 MHz this new values should be replaced with those in (1) with this new value we will get Ts=1°C at the end.…”
Section: Tests and Results Of The Thermal Peak Module Using The DImentioning
confidence: 99%
See 1 more Smart Citation
“…8 is used, this study is found in [12] for T=25 °C, f=1 MHz. As an example it can be assumed that fa 1 = fc 1 = 1 MHz this new values should be replaced with those in (1) with this new value we will get Ts=1°C at the end.…”
Section: Tests and Results Of The Thermal Peak Module Using The DImentioning
confidence: 99%
“…Despite the use of the GDS method, the originality of this work rests on the modeling and implementation of a network of thermal sensors each one is actually a ring oscillator (RO) composed of six inverters to characterize the thermo mechanical stress of a complex system, Ring Oscillator (RO) and the GDS are explained in detail in [11] and [12]. Our methodology consists on the Development of a VHDL code to model the thermal peak localization equation under Matlab tool, using the GDS (gradient Direction Sensor) technique explained before, from each cell composed of three sensors we can obtain information on the temperature distribution and partly on the position of the heat source.…”
Section: Introductionmentioning
confidence: 99%
“…Few reports [14], [15] have proposed the use of distributed sensors for monitoring temperatures in FPGAs. However, they consider only LBs in the FPGA fabric, and consequently, observed very little temperature variations across the die.…”
Section: Design and Implementation Methodologymentioning
confidence: 99%
“…There are other approaches which relay in dynamic measures to characterize the thermal behavior of the chip [8]. These techniques, opposite to ours, require not only the complete knowledge of the target architecture but also the capability to modify it.…”
Section: Related Workmentioning
confidence: 99%